2011
DOI: 10.1099/mic.0.048645-0
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of the type VI secretion systems in Pseudomonas spp.: novel clusters and putative effectors uncovered

Abstract: Bacteria encode multiple protein secretion systems that are crucial for interaction with the environment and with hosts. In recent years, attention has focused on type VI secretion systems (T6SSs), which are specialized transporters widely encoded in Proteobacteria. The myriad of processes associated with these secretion systems could be explained by subclasses of T6SS, each involved in specialized functions. To assess diversity and predict function associated with different T6SSs, comparative genomic analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 56 publications
3
116
0
Order By: Relevance
“…The variable loci were associated with type III secretion systems and effectors, type VI secretion systems and effectors, and pyoverdine siderophore biosynthesis. These structures vary among strains (37)(38)(39)(40). This finding suggests that Nanostring analysis of some transcripts across different genotypes requires the inclusion of probes that target multiple alleles, as demonstrated here for fliC, and/or DNA sequence analysis to confirm the target sequence will hybridize to the probe.…”
Section: Resultsmentioning
confidence: 91%
“…The variable loci were associated with type III secretion systems and effectors, type VI secretion systems and effectors, and pyoverdine siderophore biosynthesis. These structures vary among strains (37)(38)(39)(40). This finding suggests that Nanostring analysis of some transcripts across different genotypes requires the inclusion of probes that target multiple alleles, as demonstrated here for fliC, and/or DNA sequence analysis to confirm the target sequence will hybridize to the probe.…”
Section: Resultsmentioning
confidence: 91%
“…Recent reports suggest that Hcp and VgrG proteins are both structural and effector components of T6SSs (47,48). RPKM values for hcp-1 and hcp-2 were at least 2.5-fold lower in the ⌬vttR A and ⌬vttR B strains than in the parental strain.…”
Section: Fig 5 Swarming Diameters Of Am-19226 Wild-type and Regulatormentioning
confidence: 90%
“…Commonly, these 'orphan' hcp and vgrG genes are always encoded in the proximity of putative effector genes. 30,31 Further studies demonstrated that in T6SS-dependent delivery, the antibacterial effectors are loaded onto the secretion complex by interaction with PAAR/VgrG or by binding to the inner surface of the Hcp tube. 3 Notably, some VgrG and PAAR proteins can carry antibacterial extension domains, thus acting as secreted T6SS effectors.…”
Section: Nad (P)mentioning
confidence: 99%
“…56 The donor and recipient strains (Nal R ) were mixed together at a ratio of 3:1 after the cultures were normalized to an OD 600nm of 0.5. The mixture was then spotted on the nitrocellulose membrane placed on low-salt LB agar for 6 h incubation at 30 C. The bacterial spots were then resuspended, serially diluted in PBS and visualized on plates (eosin-methylene blue medium) containing 50 mg/ ml Nal to compare the survivals of the recipient cells co-incubated with different donor strains.…”
Section: Recipient Survival Assays For Visualization On Platesmentioning
confidence: 99%